Formulation and Evaluation of Solid Lipid Nanoparticle (SLN) of Andrographolide by Solvent Evaporation Method - Dwivedi, Chandra Prakash; Choubey, Ankur; Gupta, Naveen; Singh Rajput, Dharmendra; Kumar Pradhan, Dusmanta (Journal of Neonatal Surgery, 2025)
Andrographolide is a potential therapeutic agent that suffers from poor aqueous solubility. Nanoparticles are frequently employed to control the delivery of drugs and various growth factors to tissues/cells. Nanocarriers, in diverse formulations, have the potential to transport both synthetic and natural anticancer therapeutic drugs Therapy applications of AG are, however, seriously constrained because of poor bioavailability, short plasma half-life, and inappropriate tissue localization. Nanoparticulation of AG was therefore envisaged as a possible solution for management of liver dysfunction. Modified solvent evaporation method can be utilized for the development of lecithin nanoparticles. Polymer and crosslinking agent concentrations and sonication time are rate-limiting factors for the development of the optimized formulation. It is thus concluded that by adopting a systematic formulation approach, an optimum point can be reached in the shortest time with minimum efforts to achieve desirable rheological and in vitro release property for in situ forming system.